Elevated Temperature Does Not Substantially Modify the Interactive Effects Between Elevated CO2 and Diel CO2 Cycles on the Survival, Growth and Behavior of a Coral Reef Fish - Jarrold, Michael D.; Munday, Philip L. (Frontiers in Marine Science, 2018)
Recent studies demonstrate that diel CO2 cycles, such as those prevalent in many shallow water habitats, can potentially modify the effects of ocean acidification conditions on marine organism. However, whether the interaction between elevated CO2 and diel CO2 cycles is further modified by elevated temperature is unknown. To test this, we reared juvenile spiny damselfish, Acanthochromis polyacanthus for 11 weeks in two stable (450 and 1000 µatm) and two diel- cycling elevated CO2 treatments (1000 ± 300 and 1000 ± 500 µatm) at both current-day (29°C) and projected future temperature (31°C). We measured the effects on survivorship, growth, behavioural lateralization, activity, boldness and escape performance (fast starts). A significant interaction between CO2 and temperature was only detected for survivorship. Survival was lower in the two cycling CO2 treatments at 31°C compared with 29°C but did not differ between temperatures in the two stable CO2 treatments. In other traits we observed independent effects of elevated CO2, and interactions between elevated CO2 and diel CO2 cycles, but these effects were not influenced by temperature. There was a trend towards decreased growth in fish reared under stable elevated CO2 that was counteracted by diel CO2 cycles, with fish reared under cycling CO2 being significantly larger than fish reared under stable elevated CO2. Diel CO2 cycles also mediated the negative effect of elevated CO2 on behavioural lateralization, as previously reported. Routine activity was reduced in the 1000 ± 500 μatm CO2 treatment compared to control fish. In contrast, neither boldness nor fast-starts were affected by any of the CO2 treatments. Elevated temperature had significant independent effects on growth, routine activity and fast start performance. Our results demonstrate that diel CO2 cycles can significantly modify the growth and behavioural responses of fish under elevated CO2 and that these effects are not altered by elevated temperature, at least in this species. Our findings add to a growing body of work that highlights the critical importance of incorporating natural CO2 variability in ocean In review 3 acidification experiments to more accurately assess the effects of ocean climate change on marine ecosystems.